2018
DOI: 10.1016/j.ijhydene.2018.04.211
|View full text |Cite
|
Sign up to set email alerts
|

Dehydrogenation and rehydrogenation of a 0.62LiBH4-0.38NaBH4 mixture with nano-sized Ni

Abstract: Dehydrogenation and rehydrogenation of a 0.62LiBH 4-0.38NaBH 4 mixture with nano-sized Ni

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 89 publications
0
3
0
Order By: Relevance
“…The re-hydrogenation attempts showed that the hydrogen content decreased from 5.5 wt % to 1.1 wt % and to 0.8 wt % with no evidence of a reformation of LiBH 4 . It was suggested by Liu et al [277] that this poor cyclic stability could be improved by nanoconfinement.…”
Section: Hydrogen Sorage Properties Of Eutectic Metal Borohydride Systemsmentioning
confidence: 99%
“…The re-hydrogenation attempts showed that the hydrogen content decreased from 5.5 wt % to 1.1 wt % and to 0.8 wt % with no evidence of a reformation of LiBH 4 . It was suggested by Liu et al [277] that this poor cyclic stability could be improved by nanoconfinement.…”
Section: Hydrogen Sorage Properties Of Eutectic Metal Borohydride Systemsmentioning
confidence: 99%
“…It should be noted that the catalytic interaction of sodium borohydride with water does not require heating the reaction medium, in contrast to its thermal decomposition, which takes place at temperatures from 130 to 500 • C, even in the presence of active nanosized Ni particles [11], transition metal fluorides [12] and sodium chloride [13].…”
Section: Introductionmentioning
confidence: 99%
“…However, the above reported nanoconfinement carriers are composed of non-metallic material that can only provide a single nanoconfinement role for LiBH 4 in general. Taking into account that transition metal elements (e.g., Ni and Co) can serve as the active catalyst in improving the hydrogen storage properties of complex hydrides owing to their high electronegativity0 (Ngene et al, 2011;Liu et al, 2018;Zhang et al, 2018), a synergistic effect of nanoconfinement and catalysis would be achieved by confining LiBH 4 in nanoporous transition metal. Based on this consideration, nanoporous Ni-based alloy was prepared by dealloying of the Mn 70 Ni 30 alloy and then used as the carrier to support LiBH 4 in this work, and a significantly improved low-temperature hydrogen storage in LiBH 4 was successfully obtained.…”
Section: Introductionmentioning
confidence: 99%